Institutionalising Islamophobia in Switzerland: The Burqa and Minaret Bans. Issue 1 (1st October 2017) - Vista Eskandari; Elisa Banfi
Abstract : This article aims to analyse the legislative processes leading to forbidding the wearing of burqas and the building of minarets in Switzerland by a postcolonial approach. In 2009, a federal popular initiative amended the Swiss constitution by forbidding the construction of minarets across the Helvetic territory. At the same time, several right-wing parties have attempted to pass a general prohibition of the burqa in public spaces since 2006. As a consequence, in 2013, the canton of Tessin has adopted an article prohibiting the face covering in public spaces and, in 2016, a popular initiative for the ban of the burqa in the whole country was launched. Starting from the content analysis of parliamentary debates and legislative documents concerning these bans, hegemonic and Eurocentric narratives excluding Muslims from the national community will be examined. The article also aims at casting a new light on the interlinkages between Swiss direct democracy, populism and Islamophobia. Furthermore, the exploitation of gender aimed at reinforcing Islamophobic narratives will be analysed. In both the minarets and the burqa ban cases, the image of women has played a crucial role in justifying the right-wing discourse on Muslims and Islam in Switzerland. On the one hand, the minarets ban has occupied the Swiss public space by a propaganda poster showing a woman wearing a burqa in front of minarets erected like missiles on top of a Swiss flag. On the other hand, the burqa ban articulated its campaign around the defence of freedom and women's right as Swiss traditional values. By deconstructing political and legislative arguments against burqa and minarets, the article shows how they have encouraged the legitimacy of public Islamophobic discourses and fostered a crystallised and undifferentiated representation of the Muslims' presence in Switzerland.